RANCANG BANGUN SISTEM PENGADUAN PENANGANAN KEKERASAN SEKSUAL DI UNIVERSITAS MARITIM RAJA ALI HAJI - Indra Firdiyansyah; Riki Riki; Kiki Wulandari; Putu Rani Susanthi; Nasruji Nasruji (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
This study aims to build a complaint handling system that is fast and can monitor its progress. The method used in this study using the ultrasound matrix method and fishbone diagrams. The results show that with the system, reports of sexual violence are more recorded and can be resolved, because the perpetrators do not need to feel afraid when giving reports, and there is no longer a power imbalance between the perpetrators and the perpetrators do not feel afraid of the perpetrators of higher positions. Keywords: layanan, laporan pengaduan, fishbone, USG